PENGARUH PENGAPLIKASIAN METODE MNEMONIC TERHADAP DAYA INGAT BELAJAR SISWA PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM - Ayu Puji Rahayu; Dindin Sofyan Abdullah; Ahmad Andy Setiady (LPPM Sekolah Tinggi Agama Islam Darul Falah, 2023)
The purpose of this study was to determine whether there was an increase in students' learning memory abilities and to find out whether there were differences in students' learning memory abilities using the mnemonic method and those using conventional methods in the Syirkah subsection, the subject matter of Islamic economics principles and practices in the subjects of Islamic Religious Education at SMA Darul Falah in the 2021-2022 academic year. The research method used is quasi-experimental design. The object of research is the students of class XI. Data processing is assisted by SPSS 26 application. The results of the experimental class have a sig value of 0.154, it means that there is no significant increase. Meanwhile, the value of the regression equation is positive, namely Y=85,898 + 3.768x. Regarding the basis of decision-making, although there is no significant effect of the posttest and N-Gain scores from the experimental class, they have a positive, however weak relationship, it can be seen from the linear line that points up. The conclusion obtained from this research is that there is no difference in students' learning memory abilities between students who use the mnemonic method and students who use conventional methods. Undeniably, there are driving and supporting factors for the successful application of a learning method, as well as the use of mnemonic methods. If the supporting factors, such as student learning motivation and teacher expertise in applying this method, can improve students' learning memory abilities.